The effect of an attractant toxic sugar bait (ATSB) incorporating Bacillus thuringiensis israelensis and methoprene on mosquito populations - Thomas Kollars; Mark Carder; Mustapha Debboun; Lee McPhatter (Health for All Nations, 2024)
Background: The threat posed by mosquito-borne diseases continues to increase globally. The increase of pesticide resistance is impacting vector control and public health globally. The development and testing of new pesticides faces several challenges, e.g., time for development, high cost, and regulatory hurdles. Adapting pesticides that are currently used within integrated vector management can help alleviate these challenges. Methoprene has demonstrated reduction of larval populations and fecundity in adult mosquitoes. The objective of the study was to demonstrate the efficacy of ProVector Entobac with methoprene (Entobac M) on mosquito populations in rural sites in Southeastern Georgia. Methods: ProVector® Military Camouflage Tubes with ProVector Entobac M pesticide were placed in a grid at test sites. A positive control test site and a negative control site were used to compare results statistically. Mosquito diversity and evenness among sites were measured using Shannon Diversity Index and Equitability. Results: Deployment of ProVector® Military Camouflage Tubes with ProVector Entobac M pesticide was effective in reducing total mosquito populations. The mosquito species shared among the test sites and positive control site were similar, and the negative control site was least similar in diversity and evenness. There was variation of control within Aedes, Anopheles, and Culex genera. Discussion: The aim of the study was to demonstrate the efficacy of the ProVector Military Camouflage Tube delivery of Entobac with methoprene (Entobac M) on mosquito populations. Mosquito-borne diseases are an increasing threat to communities around the world due to invasive species and global warming. In previous studies, ProVector® Entobac™ has been validated in laboratory and field studies to control both adult and larval mosquitoes in the United States and several other countries. Application of ecofriendly and target specific pesticides with no-resistance is critical in reducing mosquito populations and the risk of vector-borne diseases. Our study demonstrated a significant decrease in adult mosquito populations due to the utilization of a target specific mosquito larvicide that has been adapted to kill adult mosquitoes.